Analisis Nilai Moral pada Novel ”the Truth about Forever (Kebencian Membuatmu Kesepian)” Karya Orizuka - Komariyah, Siti; Ramdhani, Intan Sari (Lembaga Yasin AlSys, 2022)
This research discusses the moral values contained in a novel entitled